2018
DOI: 10.1515/eetech-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Carbon supported g-C3N4 for electrochemical sensing of hydrazine

Abstract: This study reports a synthesis of carbon supported graphitic carbon nitride (g-C3N4-KBC) obtained by pyrolysis of melamine with Ketjenblack 600JD carbon (KBC) at 550°C for 4 h in a N2 atmosphere. g-C3N4-KBC oxidizes hydrazine at an onset potential 0.145 V vs. SCE close to the thermodynamic standard potential of hydrazine (0.23 V vs. SHE). In comparison to the controls, KBC and g-C3N4, g-C3N4-KBC oxidizes hydrazine at lower overpotential.Most research has tended to focus on transition metal-based catalysts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Hydrazine hydrolyzes to form N 2 H 5 + (hydrazinium ion) and OH – ions . The standard reduction potential ( E ° ) of N 2 H 5 + /N 2 [+0.23 V vs standard hydrogen electrode (SHE)] , is lower than that of Fe 3+ /Fe 2+ (+0.77 V vs SHE), which results in the reduction of Fe 3+ ions. Hydrazine reduces enough of the Fe 3+ ions of β-FeOOH at an amount of 10.8 mmol to obtain the 1:2 ratio of Fe 2+ /Fe 3+ required to produce Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrazine hydrolyzes to form N 2 H 5 + (hydrazinium ion) and OH – ions . The standard reduction potential ( E ° ) of N 2 H 5 + /N 2 [+0.23 V vs standard hydrogen electrode (SHE)] , is lower than that of Fe 3+ /Fe 2+ (+0.77 V vs SHE), which results in the reduction of Fe 3+ ions. Hydrazine reduces enough of the Fe 3+ ions of β-FeOOH at an amount of 10.8 mmol to obtain the 1:2 ratio of Fe 2+ /Fe 3+ required to produce Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…One step simple pyrolysis technique was employed for the preparation of carbon supported gCNNS-ketjenblack carbon (KBC) composite by utilizing melamine and KBC at 550 °C for 4 h in a N 2 atmosphere. The prepared metal free carbon supported gCNNS oxidized hydrazine at lower over potential [23]. An ultrafast electrochemical sensing platform developed based on gCNNS-electrochemically deposited poly(3,4-ethylenedioxythiophene) (PEDOT) composite which was fabricated through in-situ electropolymerization [24].…”
Section: Preparation Of Graphitic Carbon Nitride Nanosheets Hybrid Electrocatalystsmentioning
confidence: 99%
“…42,43 It is an emerging material in electrochemical sensing, but its application in HA detection is limited to only two studies. 40,44 Dai et al reported a flowerlike Co 3 O 4 /GCNmodified glassy carbon electrode (GCE) to detect HA, but the oxidation potential (0.5 V) is higher and detects in a narrow concentration range. Here, to further improve the performance of Co 3 O 4 for HA detection, we used the following strategies:…”
Section: Introductionmentioning
confidence: 99%
“…43 GCN can provide considerable electrocatalytic sites and has a lower overpotential for HA oxidation. 44 Co 3 O 4 /GCN hybrids have structural and compositional advantages, such as more active sites are exposed and charge transfer is fast. They benefit from the GCN layers anchored on Co 3 O 4 rods; it is expected that they enable highly sensitive oxidation of HA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation